Surgical Management of Periprosthetic Joint Infection: One-Stage Exchange - Kendoff, Daniel; Gehrke, Thorsten (The Journal of Knee Surgery, 2014)
Although it does offer some advantages, the one-staged exchange in periprosthetic joint infection (PJI) remains rare in the orthopedic world. Besides the reduced number of surgical interventions for the patients, it is usually associated with a decreased in-hospital stay and quicker mobilization. Furthermore, it might be the more cost-effective approach and allows for a reduced duration of postoperative systemic antibiotics, usually less than 14 days. Technically, the presence of a positive culture by preoperative aspiration or biopsy and respective antibiogram is mandatory. A cemented implant fixation using specified topic antibiotics, based on the antibiogram, is treatment of choice for one-staged procedures. The overall success is based on the well-defined and detailed intrahospital infrastructure, including a meticulous preoperative planning, joint aspiration regime, and aggressive intraoperative surgical approach. This article describes the one-staged exchange in infected PJI of the knee joint, which has been established 40 years ago in the HELIOS ENDO-Klinik Hamburg, Germany.
Keywords: periprosthetic joint infection; one-staged exchange; antibiotic; PJI